Landed conflict and cohabitation of communauty in Djugu Territory. The influence of superstructure upon infrastructural détermination - Kumbatulu Bakulu (IJRDO - Journal of Social Science and Humanities Research, 2019)
Currently, the landed conflicts intensification are being observed in Djugu territory has a history. This phenomenon actually damage the cohabitation of this communauty had his origin since the movements of migration of the population who lived in middle Africa. In this paper, we have been analyzing the landed strife which disrupted the Djugu Territory because of superstructural factors (political, juridical and ideological) upon infrastructural determination (economic).